Pemanfaatan Media Moodle Dan Mind Mapping Dalam Pembelajaran Pendidikan Agama Islam Di SMK Negeri 1 Blitar - Faiz Abdilla; Moh. Turmudi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
Generally, school success can be seen from the output. Evidently, Vocational High School (SMK) 1 Blitar is able to produce superior graduate quality, good personality and have skills in the world of work. Theoretically, the success of this school is not independent of the teacher's ability to implement learning strategies. And Blitar 1 Vocational School teachers have that expertise. However, inequality actually occurs in the subjects of Islamic Religious Education (PAI). The method used for the past two years is the mind mapping method using the Moodle Application. This study uses a qualitative-descriptive approach by looking at research objects in a natural setting. This study uses instruments on the ability of researchers because, in qualitative research, researchers are key instruments. Data mining techniques used interviews, observation and documentation in the field. The result is described using words in accordance with the focus of the study. Research settings in SMK I Blitar with informants, Religion Teachers, Head of Curriculum, Principal, Superintendent and graduates. The results of this study, the researchers concluded, as follows: [1] learning using the Moodle application is considered effective, because children can learn and do assignments from home without face-to-face with the teacher; [2] learning methods with mind mapping make it easier for students to learn, especially in Islamic Religious Education.